Moradores e turistas no município de Porto Rico, PR : percepção ambiental no contexto de mudanças ecológicas. - Violante, Adriano de Cerqueira (2006)
This work have aim to show the perception of the environmental dynamic of a group the dwellers and tourists in the Porto Rico city, in the north-west part of the Paraná state, Brazil that has the natural landscape and social costumes modified after the implantation of the hydro-electric station of the Rosana dam in the Paranapanema river, Porto Primavera and Itaipu dam in the Paraná river. For this goal we make as first procedure a characterization of the Conservations Units, the traditional community that live in the Conservations Units and yours problems with the low. We realize too, a brief study of the history of the Porto Rico city and the socio-economics structure. Other methodological procedure was a study categorization about a way that Porto Rico, PR makes to yours development: tourism industry. For this we realized a brief description of the tourism as industry and the tourism in the Conservations Units put the eco-tourism and sustainable tourism in projection. To know the perception of the disturb of the landscapes the Porto Rico, PR for the residents we make interviews in the local groups and tourists that visit the region and the city, totalized 30 residents and 12 tourists. The interviews are semi-structured and the analyzed of the interviews make in the light of perceptions theory, work for Ferrara (1999b) and Tuan (1980). The lines are analyzed with help the methodology proposed by Lefevre e Lefevre (2005). These theories we allow analyze / understood as both groups make insights about the region and yours alterations pos-installations of the hydroelectric station. Or, as the residents to accompanied this alterations and if these to complementation as community that, today, share with tourists. For other hand, the perceptions of the tourists are studied to know as these tourists to perceive the local and as them related with the environment. As result we have a perception these residents and tourists that indicate: a) a memory of the dwellers of the landscape of the Paraná river and the islands that, today, are modified. The evocation of these natural landscape show that the group of the residents see the yours modification as a radical and negative interference in your way of life and subsistence. The perceptions of the future of the group are contradictories, because while some residents do not like the tourists, others seem the local ecologic tourism, as a new opportunity of job; b) the tourist group see the region and city as a local to enjoy the usufruct of the natural landscape, of fishing and place to rest in the week end. This group does not seem the resident group as a traditional population; to assume them as possible workers as housekeeper and caretaker, for instance. We can affirm that, in the limits of the number of people interviews, there are a segregation of the groups and the proposition of the tourism ecologic/sportive to Porto Rico do not attend to the local dwellers that live in the region more than 40 years. We can affirm too, that whereas to the residents all this change of the natural local landscape is fundamentally connected in yours lives, to the tourists, the modifications are these that correspond in relation to the rest and use of nature. To the residents this "new" way put them to a uncertain life about your job and the your future.